The Mediating Effect of PAE, Subjective Norms, and PBC on the Impact of Diverse Learning Environments on Students Entrepreneurial Intentions - Benediktus Rolando; Herry Mulyono (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study explores the influence of diverse learning environments on the entrepreneurial intentions of undergraduate students in Tangerang, Indonesia—a region where entrepreneurial activity among students remains below national expectations. Drawing on the Theory of Planned Behavior (TPB), we examine how personal attitude, subjective norms, and perceived behavioral control mediate this relationship. A total of 312 students from six universities were surveyed using a purposive sampling method. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that while diverse learning environments significantly enhance students’ attitudes (β=0.862, p<0.001) and perceived behavioral control (β=0.872, p<0.001), they paradoxically reduce entrepreneurial intentions (β=-0.311, p<0.05). Subjective norms showed no significant effect (p=0.156), reflecting cultural nuances in collectivist societies where institutional and structural factors may overshadow social influence. These results suggest that while exposure to diversity fosters creativity and self-efficacy, it may also introduce decision complexity and risk awareness that discourage entrepreneurial action. The study extends TPB by contextualizing its limitations in non-Western settings and offers practical recommendations. These include implementing structured mentorship, industry-specific entrepreneurial curricula, and institutional support systems to help students translate diverse insights into actionable ventures. Educational institutions must balance the benefits of exposure to diverse perspectives with scaffolding mechanisms that mitigate cognitive overload and cultural dissonance. This research contributes to refining entrepreneurship education strategies in emerging economies.